2020
DOI: 10.1038/s41467-020-15585-2
|View full text |Cite
|
Sign up to set email alerts
|

Modeling germline mutations in pineoblastoma uncovers lysosome disruption-based therapy

Abstract: Pineoblastoma is a rare pediatric cancer induced by germline mutations in the tumor suppressors RB1 or DICER1. Presence of leptomeningeal metastases is indicative of poor prognosis. Here we report that inactivation of Rb plus p53 via a WAP-Cre transgene, commonly used to target the mammary gland during pregnancy, induces metastatic pineoblastoma resembling the human disease with 100% penetrance. A stabilizing mutation rather than deletion of p53 accelerates metastatic dissemination. Deletion of Dicer1 plus p53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 70 publications
1
25
0
Order By: Relevance
“…Recent studies revealed the potential therapeutic target against DICER1 ‐mutant malignancies. Chung et al 19 . reported that nortiptyline (tricyclic antidepressant) effectively suppress the growth of pineoblastoma in DICER1 ‐deleted mouse model and pineoblastoma cell line TS13‐19.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed the potential therapeutic target against DICER1 ‐mutant malignancies. Chung et al 19 . reported that nortiptyline (tricyclic antidepressant) effectively suppress the growth of pineoblastoma in DICER1 ‐deleted mouse model and pineoblastoma cell line TS13‐19.…”
Section: Discussionmentioning
confidence: 99%
“…Denatured proteins were separated on a 15% acrylamide gel and then transferred to a PVDF membrane. After blocking with 5% dry skim milk in PBST, blots were incubated with Abs against ATG5 (Novus Biologicals) 59 , p62 (Abnova) 60 , LC3 (Nanotools) 61 , and β-actin (Sigma-Aldrich) 62 . Immunocomplexes were then labelled with a HRP-conjugated anti-mouse, or with anti-rabbit antibodies, and visualised using ECL Prime Western Blotting Detection Reagent (GE Healthcare) with an ImageQuant LAS 4000 (GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%
“…Similar therapies combining checkpoint control inhibitors with other vulnerabilities in the TME or the metastatic cascade may offer even better outcomes. The generation of immune-competent mouse models that develop macroscopic metastases (e.g., [ 68 , 69 ]), provide powerful platforms to study metastasis and assess potential new drug combinations that target both the tumor and TME [ 70 ].…”
Section: The Tumor Microenvironmentmentioning
confidence: 99%